APPETITE PREDICTS INTAKE AND NUTRITIONAL STATUS IN PATIENTS RECEIVING PERITONEAL DIALYSIS. Issue 2 (6th April 2016) - Young, Valerie; Balaam, Sarah; Orazio, Linda; Bates, Annerley; Badve, Sunil V.; Johnson, David W.; Campbell, Katrina L.
SUMMARY: Background: Sub‐optimal nutrition status is common amongst patients receiving peritoneal dialysis (PD) and leads to poor clinical outcome. This population experiences multi‐factorial challenges to achieving optimal nutritional status, particularly driven by inadequate intake. Objectives: The aim of this investigation was to identify factors associated with inadequate protein intake and sub‐optimal nutritional status in patients undergoing PD. Design/Participants: This was a cross‐sectional study of 67 adult patients receiving PD (mean age 59 ± 14 years; 57% male) within a single centre. Participants were consecutively recruited and interviewed by renal dietitians, collecting: Subjective Global Assessment (SGA); quality of life (using EQ‐5D); dietary intake (via dietary interview); and appetite (using Appetite and Diet Assessment Tool). Participant demographics were obtained via survey or medical charts. Main outcome measures were inadequate dietary protein intake (<1.1 g/kg adjusted body weight/day) and malnutrition (as defined by SGA rating B or C). Results: Overall, 15 (22%) patients were malnourished and 29 (43%) had inadequate protein intake. Poor appetite (anorexia) was reported in 62% (18/29) of participants with inadequate protein malnourished patients reported anorexia versus 12 (23%) of the well‐nourished patients (p = 0.0001). Conclusion: Anorexia was a key risk factor for inadequate protein intake and malnutrition in patients undergoing PD. These findings highlight a need to closely monitor patients with appetite disturbances.